Outcomes of work-family interface in Uzbekistan - Bakhtiyor, Giyasov (Universiti Malaysia Sarawak (UNIMAS), 2013)
The purpose of this study is to investigate the relationship between work-family interface with such outcomes as family hours, family commitment, turnover intentions and work engagement among academics, administrative and technical staff in one of the higher educational institution in Uzbekistan. More specifically, the study explored the both directions of work-family enrichment (WFE) and work-family conflict (WFC) and their relationship with such outcomes as family hours, family commitment in family domain, and turnover intentions and work engagement in work domain.